The Effects of a Parental Behavior Modification Program to Prevent Pesticide Exposure Among Toddlers Living in Agricultural Areas of Thailand: An Experimental Study. - Ong-Artborirak, Parichat; Nganchamung, Thitirat; Ponrachom, Chakkrit; Wangkahart, Apiradee; Siriwat, Satinee (Journal of Multidisciplinary Healthcare, 2026)
This quasi-experimental study, using a pre-test/post-test design, aimed to assess the effect of a parental behavior modification program on pesticide exposure among young Thai children. Methods: The sample consisted of 90 families with children aged 1– 3 years who lived within 50 meters of agricultural areas, including 46 in the intervention group and 44 in the control group. Guardians in the intervention group received a behavior modification program based on the Theory of Planned Behavior (TPB), which included three training sessions and one home visit. The control group did not receive any intervention. Acetylcholinesterase (AChE) levels in toddlers were measured via finger prick in both groups at three time points: baseline, follow-up 1 (two months after the end of the intervention), and follow-up 2 (five months after the end of the intervention). Results: Linear mixed-model analysis showed that, from baseline to follow-up 1, hemoglobin-adjusted AChE (HAChE) levels in the intervention group were 1.307 U/g Hgb higher than in the control group (P = 0.047). From baseline to follow-up 2, HAChE levels were 2.332 U/g Hgb higher in the intervention group (P = 0.005), and AChE levels were also higher by 0.311 U/mL. Conclusion: These findings suggest that the parental behavior modification program can effectively reduce pesticide exposure in young Thai children, and therefore the program should be considered for implementation as part of efforts to improve health outcomes among children living in agricultural areas of Thailand.